Incidence of premature battery depletion in subcutaneous cardioverter-defibrillator patients. Insights from a multicenter registry. (19th May 2022) - Luker, J; Strik, M; Raymond-Paquin, A; Elrefai, MH; Cano Perez, O; Franqui-Rivera, H; Pott, A; Veltmann, C; Schmitt, J; Collinson, J; Van Stipdonk, AMW; Fluschnik, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: A subset of more than 35, 000 S-ICD is under FDA advisory, warning of the potential of premature battery depletion (PBD), caused by a faulty low-voltage capacitor. Based on internal data, the manufacturer projects the incidence at 3.7% after 5 years. Data independent from the manufacturer is sparse. Methods: This study was a multicenter effort of 14 centers in Europe, the US, and Canada. Consecutive patients who received a S-ICD at the participating centers were included in this retrospective analysis. Patients with the 1010 S-ICD generator model, and those without available follow-up information were excluded. Data was collected and managed using REDCap electronic data capture tools hosted at the University Hospital Cologne. The primary endpoint in this registry was device explantation, generator replacement, or generator failure. Reasons for explantation, replacement, or failure were collected. Device longevity was defined in months. It was calculated as the time from device insertion to the time of replacement, or explantation, or failure, where applicable. Premature battery depletion was defined as the occurrence of battery depletion requiring generator replacement after 60 months or less. The study complies with the Declaration of Helsinki. Ethics committee approval was obtained. This study is registered with Clinicaltrials.gov. Results: Data of n=1, 102 S-ICD devices was analyzed. The registry comprised of S-ICD generators implanted between 03/2015 and 09/2021 (43.4% A209 model and 56.6% A219 model). Of these, 611 devices (55.4%) were identified by the Boston Scientific serial number lookup tool as affected by the advisory. The mean and median follow-up duration was 2.43±1.66 and 2.29 years, respectively. During follow-up, 110 devices (10%) were explanted after 2.9±1.7 years. Battery depletion was the indication in 52. The endpoint of PBD (battery depletion after less than 5 years) was met in 37 devices (6% of the devices under advisory), after 4.1±0.6 years. In 58 cases, the S-ICD was explanted for reasons other than battery depletion. Infection (16), system upgrade (20), heart transplant or LVAD therapy (7), and inappropriate shocks or inappropriate sensing (7) were the most common indications. Discussion: This registry provides a systematic and manufacturer independent analysis of premature battery depletion in S-ICD patients. In the affected devices, the incidence of premature battery occurred in 6%. This is higher than what is projected by the manufacturer. The rate of PBD increases notably around the 4-year mark. Conclusion: S-ICD generators under advisory suffer from PBD at a higher incidence than previously reported. Patients equipped with these devices should be closely monitored.